KOMITMEN KERJA PUSTAKAWAN DALAM MEWUJUDKAN KEBERHASILAN MANAJEMEN PELAYANAN DI LINGKUNGAN DINAS PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI JAMBI: LIBRARIANS' WORK COMMITMENT IN REALIZING SUCCESSFUL SERVICE MANAGEMENT IN THE REGIONAL LIBRARY AND ARCHIVES SERVICES OF JAMBI PROVINCE - Syamsuddin (Literatify: Trends in Library Developments, 2024)
The purpose of this research is to determine the forms of commitment of librarians from the Jambi Province Library and Archives Service in realizing successful library service management. This research departs from the theory of organizational behavior initiated by Allen and Meyer which includes affective, normative and sustainable commitment. This research is a descriptive qualitative research with purposive sampling. This research involved 19 librarians and 30 informants to gather research information, while data was obtained through structured and unstructured interviews, observation and documentation. The research results show that the forms of librarian commitment are carried out through affective, normative and sustainable commitment. Affective commitment includes two forms, namely commitment to collaborate as a team with the achievement of implementing technical guidance activities 3 times and commitment to work discipline with work discipline achieved by 97%. Meanwhile, normative commitments include a commitment to completing librarian duties with each librarian achieving 10 documents per day, a commitment to evaluating the use of collections with the achievement of carrying out on-site reading surveys of 98% and a circulation of 100% per month, a commitment to user satisfaction in receiving services with an achievement in 2019 of 83, in 2020 it was 87 and in 2021 it was 92. Continuous commitment includes a commitment to developing institutions by achieving a pattern of collaboration between libraries and professional organizations, a commitment to developing librarian careers with each librarian being a resource person twice in library technical guidance activities, and a commitment to being involved in professional organizations with the achievements of every librarian active in the management of the Indonesian Librarian Association (IPI). Recommendations for normative aspects are a form of librarian commitment which includes a commitment to completing librarian tasks on time and a commitment to evaluating the use of collections, which are aspects that must be paid attention to by leaders and librarians.